EFFECT OF DIETS ENRICHED WITH VITAMIN E AND ORGANIC SELENIUM ON THE PRODUCTIVE PERFORMANCE AND MEAT QUALITY OF RAINBOW TROUT(Oncorhynchus mykiss) - Rodríguez P., Hector (2014)
The aim of this study was to evaluate diets enriched with vitamin E and organic selenium on the productive performance and meat quality of rainbow trout (Oncorhynchus mykiss). The study was carried out in the fish farm «El Ingenio» in Huancayo, Peru with 4200 juvenile trout (164 g of body weight) during 40 days. A basal diet (treatment 1), two levels of vitamin E (25 and 50 ppm) and three levels of organic selenium (0.15, 0.25 and 0.35 ppm) were used. In the study, 600 trout were assigned per each of the seven treatments, using three repetitions per treatment (n=200) in a completely randomized design. Body weight gain, feed conversion ratio, and protein efficiency ratio were evaluated. Besides, in the frozen meat content of vitamin E, selenium and total volatile basic nitrogen, and the oxidation state were determined. Data was processed by the analysis of variance, the Tukey multiple comparison test and the Dunnett’s test. The diet supplemented with 500 ppm of vitamin E and 0.35 ppm of organic selenium improved body weight gain, feed conversion ratio and protein efficiency ratio (p<0.05). Likewise, this diet improved the meat quality in relation to the control group (p<0.05) due to its capacity to store 0.23 mg of selenium per kilogram of trout meat.